Crimea as Saguntum? : a phenomenological approach to the Ukrainian crisis within the framework of a transforming post-bipolar structure - Özigci, Yunus Emre (Array, 2020)
The developments in Ukraine in 2014, namely the annexation of Crimea and the secessionist upheaval in Donetsk and Lugansk areas caused — or appeared as the content of — a rift between the “West” and Russia. The core questions of this article explore the nature of this rift and its significance on the shape of the international system in their relatedness to the Ukrainian crisis. The concepts employed in the study belong to phenomenology as adapted to the field of international relations, in order to answer to the apparent need to develop a tool that would enable us to ground the study on its subjective/intersubjective infrastructure that is adequate to the nature of the concepts of state, territory, international system and relations. Within this framework, the Ukrainian crisis and Crimean annexation appear as a positional and systemic content that marks a new temporal phase of the post-bipolar intersubjectivity. An existential framework shall thus be provided to policy contents, as a posteriori yet “real” elements of the phenomena which may be extended, on subjective/intersubjective grounds of international relations, towards positional and systemic horizons as defining and restraining fundamentals of causal interactions.